THE INFLUENCE OF FINANCIAL LITERACY ON GENERATION Z CONSUMERS IMPULSIVE BUYING BEHAVIOR WITH SELF-CONTROL AS MEDIATING VARIABLE - Febriana Ayuningtyas, Maximilla
The development of information technology in the industrial era 4.0 has affected various aspects of life, including the financial sector by shifting transaction methods to digital payments which can encourage the formation of a cashless society. In addition, the financial products offered are currently increasingly diverse and advanced, coupled with the support of e-commerce, online shopping, and malls that are scattered everywhere, which offers the ease of access for consumers in buying products. The ability to manage finances well is needed in dealing with this situation. Coupled with the fact that currently Indonesia's financial literacy index is below the average (Mastercard, 2015). As for West Java, the level of financial literacy decreased by 1.27% based on the 2019 survey. Addressing this phenomenon, Indonesian citizens, especially Generation Z who considered full of confidence, enthusiasm, and risk taker are also required to have a comparable readiness to avoid unwanted things like falling into impulsive buying behavior. The objective of this research are to examine: (1) the influence of financial literacy on consumers impulsive buying behavior; (2) the infuence of financial literacy on self-control; and (3) the influence of financial literacy on consumers impulsive buying behavior with selfcontrol as mediating variable. This study is a comparative causal research with a quantitative approach. The object for this study is Generation Z who are individuals aged 17-24 years and stayed in Bandung, Indonesia, as Bandung is one of the favorite destinations city in Indonesia to pursue higher studies. The sampling method the author used is convenience and purposive sampling. While the data collection method is through a survey using a questionnaire. The author collecting a total of 422 samples. The data analysis technique used is descriptive statistics, inferential analysis, and path analysis. The findings of this study revealed that: (1) financial literacy has a negative and significant effect on consumers impulsive buying behavior; (2) financial literacy has a positive and significant effect on self-control; and (3) self-control is able to mediate the effect of financial literacy on consumers impulsive buying behavior.